Imaging-Based Characterization of a Slco2b1(-/-) Mouse Model Using [11C]Erlotinib and [99mTc]Mebrofenin as Probe Substrates - Solène Marie; Irene Hernández-Lozano; Louise Breuil; Charles Truillet; Shuiying Hu; Alex Sparreboom; Nicolas Tournier; Oliver Langer (MDPI AG, 2021)
Organic anion-transporting polypeptide 2B1 (OATP2B1) is co-localized with OATP1B1 and OATP1B3 in the basolateral hepatocyte membrane, where it is thought to contribute to the hepatic uptake of drugs. We characterized a novel Slco2b1(-/-) mouse model using positron emission tomography (PET) imaging with [11C]erlotinib (a putative OATP2B1-selective substrate) and planar scintigraphic imaging with [99mTc]mebrofenin (an OATP1B1/1B3 substrate, which is not transported by OATP2B1). Dynamic 40-min scans were performed after intravenous injection of either [11C]erlotinib or [99mTc]mebrofenin in wild-type and Slco2b1(-/-) mice. A pharmacokinetic model was used to estimate the hepatic uptake clearance (CL1) and the rate constants for transfer of radioactivity from the liver to the blood (k2) and excreted bile (k3). CL1 was significantly reduced in Slco2b1(-/-) mice for both radiotracers (p < 0.05), and k2 was significantly lower (p < 0.01) in Slco2b1(-/-) mice for [11C]erlotinib, but not for [99mTc]mebrofenin. Our data support previous evidence that OATP transporters may contribute to the hepatic uptake of [11C]erlotinib. However, the decreased hepatic uptake of the OATP1B1/1B3 substrate [99mTc]mebrofenin in Slco2b1(-/-) mice questions the utility of this mouse model to assess the relative contribution of OATP2B1 to the liver uptake of drugs which are substrates of multiple OATPs.